THE RELATIONSHIP OF HEAT SHOCK PROTEINS TO TUBERCULOSIS INFECTION: A SYSTEMATIC REVIEW - Muim, Rosyinta; Marviella, Sephia Tiara; Zuhri, Fuad Minan (Jurnal Biosains Pascasarjana, 2025)
ABSTRAK Tuberculosis infection is a global health problem that occurs in almost every part of the world. HSPs are expressed by MTB when stimulated by stress in response to physiological pressure. We used PubMed, MDPI, and Scopus database to select eligible studied for systematic review published between January 1, 2019 and March 02, 2024. We investigated potential publication bias by examining quality assessment using the SCIRAP tool. From the articles reviewed, it was found that HSPs can play a role in TB infection both as therapeutic agents, biomarkers, and as new diagnostic agents to support the control of TB infection which is still an endemic infection. Types of HSPs that are known to play a role in TB infection are: HSPX, HSP16.3, HSP70, HSP27, and HSPR. This research concluded that HSPs are expressed by MTB under stress, and the expressed HSPs are then used as biomarker for effective diagnostic testing of TB infection, especially latent TB infection, as well as their development as therapeutic agent for making drugs for TB infection.